Boundary-value problems for differential equations unsolvable with respect to the higher time derivative - Komarnyts'ka, L. I.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For differential equations with constant coefficients unsolvable with respect to the higher time derivative, we establish conditions of the existence and uniqueness of solutions of problems with conditions local in time and periodic in space variables. We prove a metric theorem on lower bounds of small denominators appearing in the construction of solutions of the problems.